Climate warming and atmospheric deposition jointly accelerate the Antarctic Peninsula atmosphere–glacier–land–ocean mercury loop - Chengzhen Zhou; Maodian Liu; Qianru Zhang; Nikki H. Zhang; Xuejun Wang (Proceedings of the National Academy of Sciences, 2026)
Mercury (Hg) is a toxic pollutant of global concern that threatens ecosystem and human health. Its cycle is being jointly reshaped by anthropogenic emissions and polar warming, yet the response of the Antarctic system remains poorly constrained. Here, we reconstruct the past 200 y of Hg source–sink dynamics in the Antarctic Peninsula (AP), Antarctica’s fastest-warming region with the most pronounced glacier melting, by combining geochemical and isotopic records from 16 sediment cores collected across the AP shelf, with a developed observation-constrained multimedia Hg budget model. We find that despite its remoteness from anthropogenic emission sources, the modern AP shelf exhibits an Hg accumulation rate of 93 ± 58 µg m −2 y −1 , twice the global shelf average. Since industrialization, this accumulation rate has increased by 160%, making the AP one of the major hotspots of marine Hg enrichment. The model further reveals that this acceleration is driven by two coupled mechanisms: 1) enhanced atmospheric deposition and expanding open water strengthen the direct uptake of atmospheric Hg by seawater within the atmosphere–ocean loop, and 2) ice melt and erosion activate the long-overlooked atmosphere–glacier–land–ocean loop, remobilizing legacy Hg stored on land. The coupling of these two loops has increased ice melt-driven terrestrial Hg release by 550% and air–sea exchange by 350%. Thus, climate warming is turning the large historical Hg reservoir in Antarctica into an active secondary pollution source, amplifying polar Hg pollution risk.